RETRACTED: Macrophages depletion alleviates lung injury by modulating AKT3/GXP4 following ventilator associated pneumonia - Zhu, Youfeng; Chen, Yang; Xie, Di; Xia, Dong; Kuang, Huanming; Guo, Xinmin; Ning, Bo (Frontiers in Immunology, 2023)
Background: AKT3 appears to play a role in lung cancer. However, its role in ventilator-associated pneumonia is still unclear. Therefore, this study aimed to investigate the role of AKT3 in macrophages during ventilator-associated pneumonia.The mRNA level of AKT3, Data from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), The data is analyzed using the Xiantao academic analysis tool. Additionally, the roles of AKT3 in ventilator-associated pneumonia (VAP) were investigated through in vivo experiments.Results: AKT3 was differentially expressed in various normal and tumor tissues. Functional enrichment analysis indicated the immunomodulatory function and inflammatory response of AKT3 in lung cancer. Depletion of macrophages protected against lung epithelial cells and significantly decreased MMP9, MMP19, FTH, and FTL expression levels and increased GPX4 expression levels, while partially reversing the changes in macrophage. Mechanistically, macrophage depletion attenuates ferroptosis of lung epithelial cells by modulating AKT3 following VAP. Conclusion: Collectively, this study suggests the need for further validation of the immunoregulatory function of AKT3 in lung cancer. Additionally, macrophage depletion mitigates lung injury by modulating the AKT3/GPX4 pathway in the context of VAP.